Intestinal development and function of broiler chickens on diets supplemented with clinoptilolite - Wu, Q J (Asian-Australasian journal of animal sciences, 2013)
The purpose of this study was to evaluate the effect of natural clinoptilolite (NCLI) and modified clinoptilolite (MCLI) on broiler performance, gut morphology, intestinal length and weight, and gut digestive enzyme activity. A total of 240 d-old male chicks were randomly assigned to 3 treatments, each of which comprised 8 pens of 10 chicks per pen. Birds in the control group were fed the basal diet, while those in the experimental groups were fed diets supplemented with NCLI at 2% (NCLI group), or MCLI at 2% (MCLI group), respectively, for 42 d. Compared with the control, supplementation with NCLI or MCLI had no significant (p>0.05) effects on productive parameters from d 1 to 42. Supplementation with NCLI or MCLI had no influence on the relative length and weight of small intestine at d 1 to 21. But supplementation with NCLI or MCLI significantly reduced the relative weight of duodenum. Supplementation with MCLI and NCLI was associated with greater (p<0.05) villus height in the jejunal and ileal mucosa compared with those areas in the controls from d 1 to 42. However, supplementation with NCLI and MCLI had no significant (p>0.05) influence on the crypt depth in the jejunal and ileal mucosa compared with those in the controls. The addition of either NCLI or MCLI to the diet improved the activities of total protease, and amylase in the small intestinal contents. In conclusion, supplementation with NCLI or MCLI in diets improved intestinal morphology, increased the intestinal length and weigh and gut digestive enzyme activity